Nonindependent pulsed atmospheric pressure discharge sustained by a high-energy electron beam lasting 100 μsec; Soviet Physics Journal; Vol. 18, № 11 - Vychkov i. e. [Bychkov] Yu. I.; Genkin S. A.; Korolev Yu. D.; Mesyats G. A. Gennady Andreyevich; Rabotkin V. G.; Filonov A. G. (1976, 1976)
В фонде НТБ ТПУ отсутствует